A scoping Review on the Impact of Self-Stigma in Individual with Type 2 Diabetes - Isworo, Atyanti; Ekowati, Wahyu; Danismaya, Irawan (Media Keperawatan Indonesia, 2025)
Self-stigma, also known as internalized stigma, is the psychological burden that arises when individuals adopt society’s negative perceptions about their health condition. This phenomenon is commonly experienced by individuals with type 2 diabetes mellitus (T2DM) and can significantly affect their psychological well-being and self-care practices. This scoping review aims to map the various impacts of self-stigma on individuals with T2DM based on the most recent empirical evidence. The review followed the Arksey and O’Malley framework and adhered to PRISMA-ScR guidelines. A comprehensive search was conducted across nine databases, resulting in the inclusion of twelve primary studies. The data were analyzed thematically and narratively. Self-stigma was found to have multidimensional effects, encompassing psychological aspects, behavioral aspects, clinical consequences and quality of life. Contextual factors such as age, duration of diabetes, gender, and BMI influenced the degree of self-stigma experienced. Self-stigma poses a substantial barrier to effective T2DM management. Psychosocial interventions that promote self-efficacy and social support are essential to mitigate its negative effects and enhance patients’ overall health outcomes